The Effect of Inquiry-based Learning on Religious Subjects Learning Activities: An Experimental Study in High Schools - Husni, Husni (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2020)
This study aims to test the validity of inquiry learning models in making students more active in the learning process. This research using experimental methods. The experimental design uses a pretest and posttest control group, an experimental design with two groups. Research has proven that the inquiry learning model significantly makes students more active. They become more responsive, more enthusiastic, ask more questions, and are happier to find new knowledge. The group of students who learned using the inquiry learning model had higher student activities compared to the group of students who did not use the inquiry learning model. The first group of students became more diligent, more enthusiastic, asked more questions, were more active in discussion activities, and were more creative in solving problems and finding new knowledge.